The ROLE OF THE PAI TEACHER AS A ROLE MODEL IN THE FORMATION OF STUDENT DISCIPLINE CHARACTER: STUDY AT SMP KHARISMA BANGSA SOUTH TANGERANG - Slamet, Muh. Ubaidillah Alghifary; Sari, Regita Novita (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: This study was motivated by the phenomenon of declining discipline among junior high school students, such as lack of obedience to rules and weak self-control in the use of technology. In this context, Islamic Education (PAI) teachers play a strategic role as role models in shaping students' disciplinary character. Purpose: This study examines the disciplinary values taught by PAI teachers to ninth-grade Cambridge students at SMP Kharisma Bangsa Pondok Cabe Tangerang Selatan, and the strategies employed by PAI teachers as role models in shaping the disciplinary character of these students. Method: Using a descriptive qualitative approach with a case study method, data was collected through observation, interviews, and documentation. Data analysis techniques included data reduction, display, and drawing conclusions. Results: The findings indicate that the values of discipline taught by PAI teachers to students include time discipline, academic discipline, and personal discipline. The strategies implemented by PAI teachers as role models that positively impact student discipline include: establishing clear and consistent rules, instilling discipline values directly and indirectly, and fulfilling the teacher's role to the fullest as an educator, role model, facilitator, mentor, and evaluator.  Conclusion: Recommendations from this study include evaluating the values of discipline in education, improving teachers' competence as role models, and conducting further research on the impact of teachers' role models on students.